Winding Road of Child Adoption in Indonesia: Wonderful Communication Competencies for Eradicating Anxiety of the Adoption Process - Winda Hardyanti; Prahastiwi Utari (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2026)
Child adoption is a process attached to anxiety and uncertainty. This research needs to formulate ways to reduce the anxiety and uncertainty experienced by adoptive parents at the beginning of the adoption process. The research approach is carried out with a qualitative approach and using case studies. The results stated that communication competencies needed to reduce anxiety in the initial adoption process include communication orientation, conformity orientation, and utilizing significant other and internal support to reduce anxiety in the adoption process. In delivering the message of the adoption plan, the adoptive parents conveyed the message directly to the couple and used a presupposition message visualization strategy to deliver the message. In managing uncertainty, adoptive parents seek to reduce anxiety by communicating directly through proactive and retroactive processes. This research contributes to the finding of communication competencies needed to reduce the anxiety experienced by adoptive parents in the adoption process.